2009
DOI: 10.1007/s11244-008-9153-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals from Biomass: Aerobic Oxidation of 5-Hydroxymethyl-2-Furaldehyde into Diformylfurane Catalyzed by Immobilized Vanadyl-Pyridine Complexes on Polymeric and Organofunctionalized Mesoporous Supports

Abstract: Diformylfurane (DFF) has been obtained by aerobic oxidation of 5-hydroxymethyl-2-furaldehyde (HMF) with homogeneous pyridine-vanadyl complexes in homogeneous phase, with Cu and V in poly(4-vinylpyridine) crosslinked with 33% divinylbenzene (PVP) and supported on organofunctionalized SBA-15 mesoporous materials. Detailed spectroscopic characterization of the materials is provided. Catalytic results show that pyridinevanadyl complexes supported on SBA-15 are less active than when in the polymeric form. The natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…HMF can be readily oxidized to different potentially important products, such as maleic anhydride [4], 2,5-diformylfuran (DFF) [5,6], 2,5-furandicarboxylic acid (FDA) (Scheme 1) or its dimethyl ester [7][8][9][10][11]. FDA has been established by the US Department of Energy (DOE) biomass program as one of the 12 chemicals that in the future can be used as chemical building block from biomass in biorefineries [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…HMF can be readily oxidized to different potentially important products, such as maleic anhydride [4], 2,5-diformylfuran (DFF) [5,6], 2,5-furandicarboxylic acid (FDA) (Scheme 1) or its dimethyl ester [7][8][9][10][11]. FDA has been established by the US Department of Energy (DOE) biomass program as one of the 12 chemicals that in the future can be used as chemical building block from biomass in biorefineries [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Further it enhances the utilization efficiency, promotes its antioxidant system and thus, accelerates its germination and growth. The positive effects of TiO 2 could probably be due to its antimicrobial nature which can enhance strength and make the plants resistance to stress [63,64]. Therefore, we conclude that the spent catalysts which are released during the degradation experiment have no or insignificant toxic effects on seed germination (as shown in Fig.…”
Section: Effect Of Spent Catalyst On Seed Germinationmentioning
confidence: 78%
“…Other metal modified VOP did not show better activity. In 2009, Navarro et al [103] studied the aerobic oxidation of HMF with homogeneous pyridine-vanadyl complexes in a homogeneous phase, with Cu and V in poly(4-vinylpyridine) crosslinked with 33% divinylbenzene (PVP) and supported on organofunctionalized SBA-15 mesoporous materials. It was found that pyridine-vanadyl complexes in the polymeric form showed higher performance than those supported on organofunctionalized SBA-15.…”
Section: Catalytic Oxidation Of Hmf To Dffmentioning
confidence: 99%